Anthropology of the arts a reader - Bakke, Gretchen Anna; Peterson, Marina (London Bloomsbury Academic, 2017)
A comprehensive introduction to the anthropology of the arts, this is the first textbook to go beyond visual art to cover the arts more broadly. Drawing together media such as painting, sound, performance, video, and film, it presents a clear overview of the cross-cultural human experience of art. Introducing students to the basics as well as the latest scholarship, the book features: - 45 chapters which combine classic texts from anthropologists such as Pierre Bourdieu, Claude Levi-Strauss, Margaret Mead, Bronislaw Malinowski, Alfred Gell, Franz Boas, and Mary Douglas with recent scholarship by George Marcus, Tim Ingold, Roger Sansi, Christopher Pinney, Georgina Born, and others - Both theoretical and ethnographic readings, with coverage ranging from Bali, Papua New Guinea, Egypt, sub-Saharan Africa, Eastern Europe, and Australia to the United States - Introductory materials, ethnographic exercises, further reading ideas, and alternative suggestions for navigating the content based on medium, geography, theory, or ethnography Designed for classroom use, Anthropology of the Arts is invaluable for teaching and learning.
Introduction / Gretchen Bakke and Marina Peterson -- Canoes and sailing/the ceremonial building of a waga / Bronis±aw Malinowski -- Decorative designs of Alaskan needlecases : a study in the history of conventional designs, based on the materials in the U.S. National Museum / Franz Boas -- The problem defined : the need for an anthropology of art / Alfred Gell -- Art as experience / John Dewey -- The genuine article / Mary Douglas -- "A boggy, soggy, squitchy picture, truly" : notes on image making in anthropology and elsewhere / Dale Pesmen -- The science of the concrete / Claude Lâevi-Strauss -- Reputation as process / Howard S. Becker -- The recording studio as fetish / Louise Meintjes -- On weaving a basket / Tim Ingold -- Performing L.A. / Marina Peterson -- The 'art' and 'science' of handcrafting cheese in the United States / Heather Paxson -- Surface revelations : ecologies and epistemologies of rock art / Severin Fowles and Benjamin Alberti -- The historical genesis of a pure aesthetic / Pierre Bourdieu -- Music, modernism and signication / Georgina Born -- 'Marvels of everyday vision' : the anthropology of aesthetics and the cattle-keeping Nilotes / Jeremy Coote -- Piercing the skin of the idol / Christopher Pinney -- From ethnomusicology to echo-muse-ecology : reading R. Murray Schafer in the Papua New Guinea rainforest / Steven Feld -- Mansions of the Lord : architecture, interiority, domesticity / John L. Comaroff and Jean Comaroff -- Techniques of the body / Marcel Mauss -- "A gesture narrowly divides us from chaos" : gesture and word in trance time / Deborah Kapchan -- An anthropologist underwater : immersive soundscapes, submarine cyborgs, and transductive ethnography / Stefan Helmreich -- 'Joyous maggots' : the symbolism of Yolngu mortuary rituals / Howard Morphy -- Necro-utopia : the politics of indistinction and the aesthetics of the non-Soviet / Alexei Yurchak -- Incorporations : contemporary Slovene art and the body politic / Gretchen Bakke -- Deep play : notes on the Balinese cockght / Clifford Geertz -- The nature of performance / Richard Bauman -- Preliminary notes on audiences in Africa / Karen Barber -- The interpretation of culture(s) after television / Lila Abu-Lughod -- Games as the play of simulation / Katie Salen and Eric Zimmerman -- On punk and repulsion, a mist theory of society / Shane Greene -- Hollywood and the U.S.A. / Hortense Powdermaker -- The production of European high culture in Los Angeles : the J. Paul Getty Trust as articial curiosity / George E. Marcus -- Degraded images, distorted sounds : Nigerian video and the infrastructure of piracy / Brian Larkin -- Some properties of art and culture / Fred Myers -- Cultural sovereignty in a global art economy : Egyptian cultural policy and the new western interest in art from the Middle East / Jessica Winegar -- Cultures in dialogue? / Sally Price -- Fields and labs / Roger Sansi -- On ethnographic surrealism / James Clifford -- Twenty-seventh day / Katherine Dunham -- A talk with Katherine Dunham / Dorathi Bock Pierre -- A parade in Erhenrang / Ursula Le Guin -- For God's sake, Margaret : conversation with Gregory Bateson and Margaret Mead / Gregory Bateson and Margaret Mead -- I swear I saw this : drawings in fieldwork notebooks, namely my own / Michael Taussig -- Marina Abramoviâc : intersecting worlds, higher dimensions, and metastable shimmerings / Marko éZivkoviâc.
Includes bibliographical references and index.
Keywords: Art and anthropology; Arts and society; Ethnology in art